FILMSTADT IN THE VORSTADT: LOCATIONALITY IN THE FILMMAKING PRACTICE OF MIHÁLY/ MICHAEL KERTÉSZ/ CURTIZ (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
The article examines the largest and most monumental of the silent film epics produced in the Austrian republic: Sodom und Gomorrha (1922). In seeking out the film’s shooting location, an abandoned site of clay pits  and hilly grasslands at the southern edge of Vienna, the article explores what the site’s history and current incarnation as part of a Kurpark reveal about the filmmaker’s urban imaginary and the role of technology in modernizing it, and it establishes parallels between the early work he did under the name Michael Kertész and the later success of his cult classicCasablanca.